Assessing Revenue Authority Performance in Developing Countries: A Synthetic Control Approach. Issue 2 (28th January 2016) - Sarr, Babacar
ABSTRACT: In many developing countries, comprehensive reforms have been undertaken in tax administration during recent years and the implementation of semiautonomous revenue authorities (SARAs) constitutes one of their most visible expressions. To date, no comprehensive assessment has been undertaken to investigate how successful these SARAs have been in improving revenue collection in these countries. Therefore, this article attempts to fill this gap by assessing revenue collection trends in 20 developing countries after the SARA has been implemented. Using the synthetic control method, we show that in most countries, the implementation of a SARA did not significantly improve government revenues.